ANALISIS YURIDIS PERMOHONAN EUTHANASIA DALAM PERSPEKTIF HAK ASASI MANUSIA DI INDONESIA - Sunggara, Muhamad Adystia (Solusi, 2021)
Euthanasia is the act of intentionally ending a person's life with the aim of relieving his suffering or illness, for example, a patient suffering from an incurable disease has the possibility to propose ending his life by lethal injection or discontinuing treatment. This study discusses how to apply for euthanasia in the perspective of Human Rights in Indonesia and how to euthanasia from the aspect of criminal law. This research method is normative legal research with a statutory approach, by reviewing regulations related to legal issues. The results of this study are the general principle of the Criminal Code (KUHP) relating to the problem of the human soul is to provide protection, so that the right to live naturally as human dignity is guaranteed, then based on Indonesian law euthanasia is an act that is against the law and part of fulfilling Human rights, which humans are free to make their life choices which are regulated by law. Article 344 of the Criminal Code can no longer be used to ensnare euthanasia and must be revised, because the elements of euthanasia are not fully covered in the article. The conclusion in this study is that it is not easy to assess whether the act is contrary to criminal law, if it is not clear that the relationship between the criminal law and the criteria used as benchmarks, for an act which according to medical standards may escape criminal law. For this reason, criminal law should still be guided by generally accepted principles, namely actus non facit reum nisi mens sit rea or an act does not innocence, used in seeking material truth produced through proving the existence of a causal relationship between actions and consequences.